Jade mountains & cinnabar pools : the history of travel literature in imperial China - Hargett, James M. (James Morris), 1948- (University of Washington Press, 2018)
"This broad-ranging study is the first book-length treatment in English or any other European language of Chinese travel literature (youji) as a genre. The material addressed, most of which was written by members of the scholar-official class, extends from the Six Dynasties period (220-581), when the essential, characteristic elements of prose travel literature in China emerged, to fluorescence in the late Ming dynasty (1368-1644), after which the tremendous physical expansion of the Chinese empire fundamentally changed the nature of travel. James Hargett identifies and examines the works that constitute the core of China's travel-literature tradition and traces the dynamic process through which the genre developed, as it incorporated interplay among authors and audiences, literary milieus, and cultural institutions. Travel literature's inclusion of a variety of writing styles and purposes has made it hard to delineate. Hargett finds, however, that classic pieces of Chinese travel literature present a coherent prose narrative of the physical experience of a journey through space towards an identifiable place; are written in essay or diary format, usually as an "account" (ji); describe places, phenomena, and conditions, accompanied by authorial observations, comments, and even personal feelings; include sensory details; and narrate movement through space and time. These accounts based on first-hand observation provide windows into places unknown to the reader, or new ways of seeing familiar places. They also reveal much about the author, his values, and his view of the world, and these features in turn tells us about the author's society, making travel literature a rich source of historical information"--